2022
DOI: 10.3389/fmed.2022.929880
|View full text |Cite
|
Sign up to set email alerts
|

Acute oxalate nephropathy: A potential cause of acute kidney injury in diabetes mellitus—A case series from a single center

Abstract: BackgroundAcute oxalate nephropathy (AON) is an uncommon condition that causes acute kidney injury (AKI), characterized by the massive deposition of calcium oxalate crystals in the renal parenchyma. In previous studies, urinary oxalate excretion has been found to be increased in patients with diabetes mellitus (DM). Here, we report a case series of diabetic patients with AKI with biopsy-proven AON, aiming to alert physicians to the potential of AON as a trigger of AKI in diabetic patients in clinical practice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Treatment of oxalate nephropathy remains largely empirical and should be initiated immediately including high fluid intake, a low-oxalate and low-fat diet, and supplements that could improve the solubility of oxalate, such as calcium, citrate, and sodium bicarbonate, aiming to decrease both plasma and urine oxalate concentration [12, 72, 73]. Pancreatic enzyme therapy, intensive therapy of inflammatory bowel disease, and avoiding abuse of orlistat could be considered depending on the underlying causes [5].…”
Section: Therapies For Hyperoxaluria and Oxalate Nephropathymentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment of oxalate nephropathy remains largely empirical and should be initiated immediately including high fluid intake, a low-oxalate and low-fat diet, and supplements that could improve the solubility of oxalate, such as calcium, citrate, and sodium bicarbonate, aiming to decrease both plasma and urine oxalate concentration [12, 72, 73]. Pancreatic enzyme therapy, intensive therapy of inflammatory bowel disease, and avoiding abuse of orlistat could be considered depending on the underlying causes [5].…”
Section: Therapies For Hyperoxaluria and Oxalate Nephropathymentioning
confidence: 99%
“…Using in vitro models, Taguchi et al [ 70 ] showed that M2 macrophages have a significant ability to phagocytose CaOx monohydrate crystals and prevent crystal adherence to renal tubular cells, whereas M1 macrophages facilitated renal crystal formation. Kusmartsev et al [ 71 ] demonstrated that human macrophages in vitro are capable of phagocytizing and degrading calcium oxalate crystals produced naturally in the kidney. Kidneys developing CaOx crystals express several pro-inflammatory cytokines, crystal-related molecules, including osteopontin, CD44, and MCP-1, and adhesion-related genes, such as C3, FN , and Vcam1 .…”
Section: Oxalate Nephropathy and Kidney Injurymentioning
confidence: 99%
See 1 more Smart Citation